Analysis of Electric Low Entry Microbus Chassis Strength by Using Finite Element Method - Assa Affitra Ilham Alifian; Widya Aryadi; Andri Setiyawan (Jurnal Inovasi Mesin, 2026)
Chassis is a component of a vehicle that functions as a support for all components and the weight of the vehicle such as the body, engine, transmission, suspension, to the load of passengers or goods. This study aims to determine the value of von mises stress, displacement, and safety factor, from each variation of the chassis thickness tested. This study uses a finite element simulation method with SolidWorks 2022 software to obtain von mises stress, displacement, and safety factor values from various variations of chassis thickness. The results of the finite element method simulation produce data in the form of von mises stress, displacement, and safety factor from 3 chassis thicknesses, the data also shows that the chassis with a thickness of 4mm has the most ideal results